The Conducive Environment: J.J.R. Jolobe’s Innovative Work (Global Journal of Human-Social Science, 2025)
J J R Jolobe Imbongi Yomnqamlezo1 is one of the pioneering Xhosa writers who also expressed himself through translation both from English to isiXhosa and vice versa He proved himself not only to be a distinct man of letters but also as an innovator and pioneering linguist Steeped in the foreign culture of British imperial mission work a hand-maiden for both colonialism and apartheid in South Africa he played many roles Incrementally so ranging from the much tribalised positive socio-economic impacts of the 14th May 1835 Mfengu milkwood covenant to the effects of mission education Jolobe found himself in quite a fertile ground to prosper both spiritually and intellectually He was not only a beneficiary of colonialism but also a protector of his culture and his people This paper seeks to look at the flip side of colonialism that is the positive role it played in developing Xhosa intellectual giants like Jolobe
Keywords: imbongi yomnqamlezo; translation; linguist; mission work; colonialism; milkwood covenant; fertile ground